Chorionic gonadotropin in toxemia gravidarum - Ferrand C., José (2015)
In 6 patients with pre-eclampsia, 4 with convulsive eclampsia and 5 chorionic gonadotropin hyperemesis gravidarum were measured in blood serum using prepubertal female rats according to the method of Frank-Berman. The findings are compared with averages normal limits and equal gestational age. In 4 cases the sample was obtained in the post-partum from the second to the fourth day postpartum maximum. In all gonadotropins were dosables; a) persist even extremely low in February (500 us positive r, r refusal to 1,000 US)....; b) within normal limits term gestation (2,000 US r positive, negative to 3,000) on the second day postpartum in a case of convulsive eclampsia in a twin pregnancy and..; c) above normal limits in a case of pre-eclampsia on the fourth day postpartum (3.500 to 4.000 pcs. r.) in a multiparous, 11th gestation repeated previous history of hyperemesis in pregnancy. In other cases the sample was obtained before birth except for a case that we include in this group given the short time since the birth when removed 12 shows (3 hrs. 45 's.). In a case of convulsive eclampsia marginalized figure the upper limits of normal and in another was within normal limits. Three cases of pre-eclampsia had higher values than normal (including the one that gave birth 3 hrs. 45 's. Above) and fourth marginalized the upper limits of normal. Of the 5 cases of hyperemesis gravidarum, a four months pregnant gave higher than normal (more than 5,000 rs. H.) Figures. Another 5 were around the second month of pregnancy, of which 1 gave a figure within the upper limits of 10 regular (positive 30,000 to negative 35,000 pcs. R.) And the other 3 were within normal limits (positive 20,000, 30,000 Negative us. r.).